The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/pon.4901
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial distress and utilization of professional psychological care in cancer patients: An observational study in National Comprehensive Cancer Centers (CCCs) in Germany

Abstract: Objective: The study aimed to assess cancer patients' use of psychological care and its correlates in a large sample of cancer patients in Comprehensive Cancer Centers (CCCs) in Germany.Methods: In a multicenter study in Germany, cancer patients with various diagnoses were evaluated for self-reported use of psychological support. We measured psychological distress, depression and anxiety, quality of life, and social support with standardized questionnaires and analyzed its association with the utilization of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
50
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 24 publications
9
50
0
1
Order By: Relevance
“…Psychosocial distress showed the strongest association with the decline for psycho‐oncological support, ie, low psychosocial distress was predictive of decline. This result is in line with the majority of studies; contradictory results, however, have also been reported . In addition, not feeling depressed was also uniquely associated with decline.…”
Section: Discussionsupporting
confidence: 90%
“…Psychosocial distress showed the strongest association with the decline for psycho‐oncological support, ie, low psychosocial distress was predictive of decline. This result is in line with the majority of studies; contradictory results, however, have also been reported . In addition, not feeling depressed was also uniquely associated with decline.…”
Section: Discussionsupporting
confidence: 90%
“…We enrolled adults with cancer from CCCs in Germany for this multicenter, observational longitudinal study. Details of the study are described elsewhere [16]. Briefly, we aimed to investigate and analyze the use and (non-use) of professional psychological care and possible influencing factors.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…However, with only 6.5% of lung cancer patients in the Waikato region being referred during the study period, the number of patients being referred is lower than reported in other countries 15,16 and may represent an unmet need in NZ, particularly for Māori. Thus, it is imperative that psychosocial support services continue to be made accessible (and be appropriately delivered to) both Māori and non-Māori lung cancer patients within the Waikato region of NZ.…”
Section: Chepulis Et Al 1589mentioning
confidence: 63%
“…Lastly, whilst this study has not quantified the efficacy of the CPSSS in alleviating patient psychological distress, the service is a positive addition, particularly given the highly distressing nature of lung cancer, the poor prognosis and stigma associated with the disease. However, with only 6.5% of lung cancer patients in the Waikato region being referred during the study period, the number of patients being referred is lower than reported in other countries and may represent an unmet need in NZ, particularly for Māori. Thus, it is imperative that psychosocial support services continue to be made accessible (and be appropriately delivered to) both Māori and non‐Māori lung cancer patients within the Waikato region of NZ.…”
Section: Discussionmentioning
confidence: 99%